Vitamin K Effects on Gas6 and Soluble Axl Receptors in Intensive Care Patients: An Observational Screening Study - Ulf Schött (MDPI AG, 2021)
Growth arrest-specific gene 6 protein (Gas6) is avitamin K-dependent tissue bound protein. Gas6 has been shown to promote growth and therapy resistance among different types of cancer as well as thromboembolism. The aim of this prospective screening study: ClinicalTrials.gov; Identifier: NTC3782025, was to evaluate the effects of intravenously administered vitamin K1 on Gas6 and its soluble (s)Axl receptor plasma levels in intensive care patients. Vitamin K1 was intravenously injected in non-warfarin treated patients with prolonged Owren prothrombin time international normalized ratio (PT-INR) > 1.2 and blood samples were retrieved before and 20–28 h after injection. Citrate plasma samples from 52 intensive care patients were analysed for different vitamin K dependent proteins. There was a significant, but small increase in median Gas6. Only one patient had a large increase in sAxl, but overall, no significant changes in sAxl Gas6 did not correlate to PT-INR, thrombin generation assay, coagulation factors II, VII, IX and X, but to protein S and decarboxylated matrix Gla protein (dp-ucMGP). In conclusion, there was a small increase in Gas6 over 20–28 h. The pathophysiology and clinical importance of this remains to be investigated. To verify a true vitamin K effect, improvement of Gas6 carboxylation defects needs to be studied.